Examining the role of financial innovation on economic growth: Fresh empirical evidence from developing and developed countries - Mohd Hammad Naeem; Mohammad Subhan; Shabbir Alam; Mamdouh Abdulaziz Saleh Al-Faryan; Mohammad Yameen (Cogent Economics & Finance, 2023)
From an economic prospective, the relationship between financial innovation and economic growth has always been a critical aspect of the financial system. However, this relationship has not recieved extensive attention in academia. Therefore, this study examines the effect of financial innovation on economic growth in the context of developing and developed countries using 92 cross-sectional data over the period of 2002 to 2020, the fixed effect method of panel regression has been applied to examine the relationship between financial innovation and economic growth. This study has compared the results of developing and developed countries using different combinations of explanatory variables. The results of this study depict that various combinations of variables have varied impacts on dependent variable. This study has revealed the negative relationship between financial innovation and economic growth. However, domestic credit to private sector banks has the best proxy for financial innovation. This study suggests that regulators should focus on encouraging and discouraging financial innovation based on its impact on the economy.
Keywords: 330; economic growth; financial development; Financial innovation; random and fixed effect model